An outbreak of Mycoplasma pneumoniae in children after the COVID-19 pandemic, Shanghai, China, 2023 - Zhu, Xunhua; Liu, Pengcheng; Yu, Hui; Wang, Libo; Zhong, Huaqing; Xu, Menghua; Lu, Lijuan; Jia, Ran; Su, Liyun; Cao, Lingfeng; Zhai, Xiaowen; Wang, Yi; et al. (Frontiers in Microbiology, 2024)
Background During the coronavirus disease 2019 (COVID-19) pandemic, the infection of Mycoplasma pneumoniae (MP) decreased significantly. At the beginning of the summer of 2023, there was an increasing trend of MP infection in China and the MP pneumonia (MPP) is surging when it comes to the school season and lasts for several months which has attracted widespread attention. Objective This study aims to investigate the prevalent characteristics of the MP and the difference between the COVID-19 pandemic and the post in Shanghai, China. Methods The demographic information and the results of laboratory pathogen detection from July 2021 to May 2024 were collected and analyzed to find out the prevalent characteristics of MP. Two periods, during the COVID-19 pandemic and the post-pandemic, were divided and compared. The P1 genotyping and macrolide resistance-associated gene of 23 s rRNA were detected using the remaining MP-positive samples. Results During the COVID-19 pandemic, the prevalence of the MP has significantly decreased. Female children are more susceptible to MP infection than the male. The school-aged group (>6 years) had the highest infection rate. The rate of MP P1 genotype during post panel is higher than that during COVID-19 pandemic, which is dominant from July 2021 to May 2024, while the macrolide-resistant associated mutations (A2063G) keep high percentage during or post pandemic. Conclusion After the COVID-19 pandemic, an outbreak of MP infection occurred from summer onwards in 2023 with children in Shanghai, China. Immunity debt and high rate of macrolide-resistance may take effects in this MP epidemic. Continuous surveillance of MP is necessary to help to alert the prevalence of MPP.